Penerapan Model Problem Based Learning Untuk Meningkatkan Kemampuan Berpikir Kreatif Matematis Siswa Di SMA Negeri 2 Medan - Yuki Indayanti; Hidayat Hidayat; Ramadhani Ramadhani; Atika Erlina Nasution; Yusni Utami (Departement of Mathematics Education, 2024)
The purpose of this study is to determine whether and how the Problem Based Learning approach enhances students' capacity for mathematical creativity. The research was conducted in two cycles using Classroom Action Research (PTK). A total of 36 students from class XI at MIPA 7 SMA Negeri 2 Medan participated in the study. To be considered effective, this research must achieve the following criteria: (1) Students' mathematical creative thinking capacity must rise by 85% or more, falling into the medium group; and (3) Both student and teacher observations must indicate a good level of performance. The study found that while the average score on the first ability test was 58.85, it increased to 67.12 during cycle I and 84.78 during cycle II. Along with an increase in initial ability test scores, there was a rise in classical completeness; in cycle I, that number rose to 24 students (61.11%), and in cycle II, it reached 36 students (100%). The findings suggest that the PBL approach can help students develop their critical thinking skills.